STRATEGI DISTRIBUSI DAN PROMOSI MI GLOSOR SEBAGAI MAKANAN KHAS KOTA BOGOR - Jumiono, Aji; Harun, Asep; Dihansih, Elis (Jurnal Ilmiah Pangan Halal, 2020)
Distribution and promotion strategy is a very important thing that must be done by a company to face competition in order to continue to grow and earn profits according to company targets. Through this research, a study of distribution strategies and promotion of glossy noodles as a typical food of Bogor City using the A’WOT method, an analytical method that combines the Analytical Hierarchy Process (AHP) method and the SWOT (Strength-Weakness-Opportunity-Threatness Analysis) method. The results showed: 1) The position of distribution strategy and promotion of the development of mi glosor in the city of Bogor in the internal-external quadrant matrix in quadrant IV, which requires caution, 2) The estimation results of internal factors and external factors indicate the marketing position is in quadrant III with the strategy conservative, 3) The results of AHP analysis found that opportunity factors are the main factor in the development of distribution, 4) Priority of distribution strategies and promotion of mi glossos in Bogor City are: a) Utilizing information technology advancements to increase promotion in the middle class, b) Utilizing market share by increasing production capacity, c) Utilizing market share to increase regular customers with high quality noodles and raw materials, d) making glossy noodles as a typical Bogor product, e) Increasing the shelf life of glossy noodles and packaging quality in order to compete in the market, f ) Increase capital, production technology, production capacity and promotion through government support and assistance, g) Increase cooperation with customers and i) maintain the quality of the noodles in order to compete. Keywords: Distribution and Promotion Strategy, Gloss Glossary, A’WOT, Bogor City